Membangun Lingkungan Belajar Menyenangkan untuk Mengatasi Kecemasan Matematika dan Meningkatkan Keterlibatan Siswa Kelas I SD Sekolah XYZ Jakarta - Juni Arsih Sinaga (Jurnal Syntax Admiration, 2024)
This research aims to explore the use of Math Centers as a enjoyable learning environment to address mathematics anxiety and improve engagement in 1st-grade students at XYZ Elementary School. Mathematics plays a crucial role in the elementary education curriculum, contributing significantly to the development of logical understanding and problem-solving skills for students. However, the high level of mathematics anxiety and low student engagement pose challenges in the early learning process. This qualitative research involved one 1st-grade class with 20 students as the research subjects. Data were collected through classroom observations, test results, and interviews with both teachers and students. The findings indicate that 1st-grade students participating in Math Centers exhibit low mathematics anxiety and active engagement in the classroom. Students also tend to enjoy mathematics lessons in the Math Centers setting compared to regular classes. The varied activities provided in Math Centers make mathematics no longer perceived as a dull and intimidating subject. The implementation of Math Centers at XYZ Elementary School will be carried out regularly every Friday to sustain students' interest in mathematics, reduce anxiety, and motivate them to actively participate in the learning process.